GM-002 Training of health professionals in the good use of insulin: satisfaction survey. (25th February 2017) - Orloff, M; Agullo, M; Ferreira, V; Boronad, C
Abstract : Background: Insulin is one of the high risk drugs. In hospitals, low level of information of nursing staff is identified as a risk factor for poor glycaemic control and more severe iatrogenic events. Therefore, practical training conducted by a diabetologist and a pharmacy resident was proposed for nurses. This training concerns the management of poor glycaemic control and the appropriate use of insulin in acute situations. Purpose: The aim of this study was to assess the usefulness of this training for nurses. Material and methods: A questionnaire was developed to evaluate the satisfaction of nurses participating in the training. It contained 7 questions on training documents, content and themes that nurses would like to see improved. Results: 17 nurses from 7 different care units replied to the questionnaire. This training was considered as 'very useful' by 11 nurses (65%) and 'indispensable' by 6 nurses (35%). 14 nurses (82%) 'fully agreed' that this training had allowed expansion of their knowledge and 3 nurses (18%) 'rather agreed'. All said they had acquired new knowledge, especially about insulin administration, transport and storage modalities (6 nurses, 35%) or management of poor glycaemic control (9 nurses, 53%). 15 nurses (88%) had no need to address other topics. 2 nurses thought that some matters could have been explored more, such as actions to be taken in case of emergency, different types of insulin and handling of insulin pumps. All affirmed that this training will lead to a change in their practices. Conclusion: This training was considered necessary and satisfying by all nurses. Some areas need to be explained more. Training sessions will be established regularly, and their impact may be assessed by a practice audit. Finally, collaboration between diabetologists and other care units will be considered to develop protocols for management of emergency situations. No conflict of interest